AHLUSSUNNAH WAL JAMA'AH LEADERSHIP IN ISLAMIC EDUCATION DEVELOPMENT - Subaidi Subaidi; Abdul Wahab; Sukarman Sukarman; Isrohmawati Isrohmawati; Muhammad Dhiyaul Haq (PEDAGOGIK : JURNAL PENDIDIKAN, 2025)
Leadership in Islamic higher education faces increasingly complex challenges in maintaining Islamic identity while responding to the demands of educational transformation and institutional competitiveness. This study aims to explore Aswaja-based leadership and its contribution to the development of Islamic education. Employing a qualitative case study approach, data were collected through in-depth interviews, observations, document analysis, and student questionnaires, and subsequently analyzed using the Miles and Huberman interactive analysis model. The findings reveal that the core values of Ahlussunnah Wal Jama'ah, namely tawassuth, tasamuh, tawazun, i'tidal, and uswah hasanah, which have been systematically institutionalized through participatory governance, transparent decision-making, academic management, organizational culture, student character development, and strategic collaboration with external stakeholders. These values function not only as theological principles but also as operational leadership mechanisms that strengthen institutional legitimacy, enhance educational quality, and ensure organizational sustainability. Accordingly, the findings confirm the existence of an integrated Aswaja-based leadership model that bridges the gap between the normative values of Islam and their practical implementation in higher education governance.